CAMILLE BEAUTY'S DIGITAL MARKETING STRATEGY AS AN EFFORT TO INCREASE PRODUCT SELLING POWER - Aliya Yuniar Salsabila Setiawan Putri; Nur Maghfirah Aesthetika (PT. Antis International Publisher, 2024)
General Background: In the contemporary business landscape, companies are increasingly competing to deliver fast, convenient, and high-quality services, particularly within the beauty industry, which has gained significant traction among young women. Specific Background: The proliferation of social media platforms has emerged as a vital marketing tool for beauty brands, enhancing their reach and engagement with potential customers. Knowledge Gap: Despite the recognized importance of digital marketing strategies, there is a paucity of comprehensive research analyzing the specific indicators that contribute to the selling power of beauty products in an online context. Aims: This study aims to evaluate the digital marketing strategies employed by Camille Beauty and their effectiveness in enhancing product sales. Results: Utilizing a descriptive qualitative methodology, the research identifies five key indicators—accessibility, interactivity, entertainment, credibility, and informativeness—that Camille Beauty integrates into its digital marketing approach. The implementation of these indicators has significantly boosted sales turnover and fostered customer trust. Novelty: This research uniquely highlights the critical role of these five digital marketing indicators in the beauty sector, providing a framework for other brands to enhance their online presence and sales effectiveness. Implications: The findings underscore the importance of a well-rounded digital marketing strategy, suggesting that brands in the beauty industry can achieve greater market penetration and consumer loyalty by focusing on these specific dimensions. This study contributes to the growing body of literature on digital marketing strategies, offering practical insights for beauty businesses aiming to thrive in a competitive digital marketplace.